Combining quantitative and qualitative data in business cycle research - E. Smit (South African Journal of Business Management, 1986)
In this article a leading indicator of the South African business cycle is proposed which combines the traditional quantitative data inputs with qualitative data. The integration is achieved via the Kalman filter technique. It is shown that this model surpasses the traditional approaches in accuracy.
Keywords: 650